"Thank You, Sorry, Love" (TSL) Therapy With North Korean Refugee Women: A Pilot Study. (November 2016) - Kim, Hee Jin; Kim, Jae Yop; Kim, Dong Goo
Objectives: This study was designed to evaluate the effectiveness of The "Thank You, Sorry, Love" (TSL) family therapy program in potentially improving the marital relationships and health of North Korean refugee women. Methods: The participants included 12 married North Korean female refugees in their 20s to 40s. Using a blinded assignment, six received the TSL family therapy program and six did not receive any treatment. Pretests (just before the program), posttests (just after termination of the program), and follow-up tests (1 month after termination of the program) were conducted. Results: The program participants experienced a statistically significant decrease in marital violence and an increase in their total antioxidant activity levels. Conclusions: TSL family therapy has the potential to contribute to improving the lives of traumatized North Korean refugee women. Larger scale replication studies involving random assignment would be a useful next step in evaluating the TSL program.